The effectiveness of propolis on the healing period of recurrent aphthous stomatitis - Han, Foo You; Setiadhi, Riani; Sudjarwo, Indrati (Universitas Padjadjaran, 2012)
Introduction: Propolis®, also known as bee glue, is a substance acquired from the bee hive, which contain antimicrobial, antiviral and antifungal properties. The aim of this research was to identify the best concentration of propolis® that is effective for healing period of Recurrent Aphthous Stomatitis (RAS). Methods: This research was experimental study and the sample are patients who have Recurrent Aphthous Stomatitis during the extent of the research at Rumah Sakit Gigi dan Mulut, Bandung, Indonesia. the patients were given Propolis® of either 0.5% or 1.0% concentration randomly. Results: Using the Kolmogorov-Smirnov test, the data is tested for normality of patients whom are applying Propolis® cream at concentration of 0.5% and 1%. The average time taken for the subject with 0.5% Propolis® cream to fully heal were 5 days, while those with 1.0% Propolis® cream required 6 days. From the t-test for equality of means, where 0.140 > 0.05, we can conclude that the difference is not significant between subjects that were given Propolis® cream at 0.5% concentration compared with subject given with 1.0% concentration of Propolis® cream.The result shows that Propolis at 0.5% concentration provides an average healing period of 5 days while propolis at 1.0% on an average of 6 days for the healing of RAS. Conclusion: Propolis at 0.5% is more effective compared to 1.0% for healing period of Recurrent Aphthous Stomatitis.